Research on Calculation Methods of Meshing Intervals of Cycloid Pin Gear Transmission - Wu Zhenyu; Wang Siming; Li Ling; Du Fangxin (Jixie chuandong)
In response to the problems of no suitable constraint conditions in the optimization process of tooth profile modification of cycloidal pin wheel transmission, difficulty in determining the modification amount of cycloidal gear tooth profile in reverse engineering, and the inability to obtain the meshing interval when studying the characteristics of cycloidal pin wheel transmission, research has been conducted on the method for determining the meshing intervals of cycloidal gears. Firstly, the stiffness analysis is performed to determine the main components that affect the stiffness. Then, through the contact stiffness analysis of the key components, the torsional stiffness model of the needle roller bearing, the tapered roller bearing and the meshing point of the cycloid are established respectively.On this basis, the torsional stiffness equation of the cycloid with needle roller bearings, tapered roller bearings and with the torsion angle of the whole machine as variables is deduced.Finally, according to the continuity principle of meshing points, all the meshing intervals whose sum of torsional stiffness of meshing points is approximately equal to the torsional stiffness of cycloidal wheels are calculated, and according to the principle that the initial meshing point of cycloidal wheels does not change with the increase of load, the feasible meshing intervals under different loads are finally screened. The analysis results of this method are basically consistent with the actual situation, and there is no need to disassemble the reducer, which can provide necessary reference data for the design and optimization of cycloid pin gear transmission.